Bulk and Surface Stabilization Process of Metastable Li-Rich Disordered Rocksalt Oxyfluorides as Efficient Cathode Materials. Issue 12 (1st December 2022) - Shirazi Moghadam, Y.; El Kharbachi, A.; Melinte, G.; Diemant, T.; Fichtner, M.
Abstract : Manganese based disordered rocksalt systems have attracted attention as Co-free and high capacity cathode materials for Li-ion batteries. However, for a practical application these materials are considered as metastable and exhibit too limited cyclability. In order to improve the structural stability of the disordered rocksalt Li1+x Mn2/3 Ti1/3 O2 Fx (0 ≤ x ≤ 1) system during cycling, we have introduced a mild temperature heat treatment process under reducing atmosphere, which is intended to overcome the structural anomalies formed during the mechanochemical synthesis. The heat-treated samples presented better electrochemical properties, which are ascribed to a structural defect mitigation process both at the surface and in the bulk, resulting in improved crystal structure stability. In addition, the optimized particle size and the smaller BET surface area induced by the recrystallization contributes to the observed enhanced performance. Among the studied compositions, the heat treated Li2 Mn2/3 Ti1/3 O2 F sample displayed better electrochemical performance with a discharge capacity of 165 mAh g −1 after 100 cycles at 0.1 C (∼80% of the initial capacity), when combined with further conditioning of the cells. The results point explicitly towards a guided stabilization approach, which could have a beneficial effect regarding the application of DRS oxyfluoride materials for sustainable LIBs.